Atlantic Meridional Overturning Circulation Response to Idealized External Forcing - Park, Wonsun; Latif, Mojib (Climate Dynamics, 2012)
The response of the Atlantic Meridional Overturning Circulation (AMOC) to idealized external (solar) forcing is studied in terms of the internal (unforced) AMOC modes with the Kiel Climate Model (KCM), a coupled atmosphere-ocean-sea ice general circulation model. The statistical investigation of KCM’s internal AMOC variability obtained from a multi-millennial control run yields three distinct modes: a multi-decadal mode with a period of about 60 years, a quasi-centennial mode with a period of about 100 years and a multi-centennial mode with a period of about 300–400 years. Most variance is explained by the multi-centennial mode, and the least by the quasi-centennial mode. The solar constant varies sinusoidally with two different periods (100 and 60 years) in forced runs with KCM. The AMOC response to the external forcing is rather complex and nonlinear. It involves strong changes in the frequency structure of the variability. While the control run depicts multi-timescale behavior, the AMOC variability in the experiment with 100 year forcing period is channeled into a relatively narrow band centered near the forcing period. It is the quasi-centennial AMOC mode with a period of just under 100 years which is excited, although it is heavily damped in the control run. Thus, the quasi-centennial mode retains its period which does not correspond exactly to the forcing period. Surprisingly, the quasi-centennial mode is also most strongly excited when the forcing period is set to 60 years, the period of the multi-decadal mode which is rather prominent in the control run. It is largely the spatial structure of the forcing rather than its period that determines which of the three internal AMOC modes is excited. The results suggest that we need to understand the full modal structure of the internal AMOC variability in order to understand the circulation’s response to external forcing. This could be a challenge for climate models: we cannot necessarily expect that the response to external forcing is realistically captured by ...